Diagnostic dilemma in female genital tuberculosis- staining techniques revisited - Deepak K Singh; Rajat Jhamb; Iqbal R Kaur; Namita Srivastava; Bineeta Kashyap (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2013)
Background: Tuberculosis (TB) is an increasing public health concern worldwide. On a global scale it has a devastating impact in developing nations. Genital TB, an extrapulmonary form, is not uncommon particularly in areas where pulmonary TB is prevalent. Genital TB may be asymptomatic or may even masquerade as other gynaecological conditions; hence, diagnosis requires a high degree of suspicion and the use of appropriate investigations. Objective: This study attempted to identify endometrial TB in endometrial biopsies taken from women evaluated for infertility by comparison of various staining techniques. Materials and Methods: A comparative cross sectional study was conducted from February 2011 to April 2011 in Guru Teg Bahadur Hospital, New Delhi. Endometrial biopsy specimens from 55 endometrial TB suspects were stained for acid fast bacilli by Ziehl Neelson staining and Gabbet staining. The biopsy samples were also subjected to Auramine Phenol fluroscent staining and H and E staining. Culture on Lowenstein Jensen medium was taken as the gold standard. Results: Three samples were culture positive giving positivity rate of 5.4%. Considering culture as the gold standard the senstivities of ZN, Gabbet, fluorescent and H and E staining were 33, 33, 66, and 66% respectively while their specificities were 100, 100, 98, and100% respectively. Conclusion: Combination of fluorescent staining techniques along with one of the acid fast staining techniques or histopathology achieves sufficient sensitivity and specificity for the diagnosis of female genital tuberculosis. There is an urgent need for developing definitive diagnostic methods to make a conclusive diagnosis of genital TB.